Library book selection - Ranganathan, S. R. (New Delhi : USB Publishers Distributors Ltd., 1989)
Works of Dr. Shiyali Ramamrita Ranganathan (S.R. Ranganathan) need no introduction. They are renowned not because they cover certain facet of library and information science, but because they have been written by the father of library science in india, Dr. Ranganathan. These library science classics have been reprinted to make Dr. Ranganathan's work available to the current generation of librarians and for those to come.
Includes index.
Keywords: Book selection